Low birthrates and high levels of female reproductive inactivity may characterize the reproductive biology of wild Peruvian red uakaris (Cacajao calvus ucayalii). Issue 1 (16th December 2014) - Mayor, Pedro; Bowler, Mark
Abstract Background Birthrates are key parameters for population models and hunting sustainability analyses frequently used in conservation, but for many rare species, these data do not exist. We examine the reproductive organs of endangered red uakari monkeys to calculate birthrates in the wild. Methods We collected reproductive organs from wild uakari monkeys hunted for subsistence by indigenous hunters and examined them for embryos or fetuses. We extrapolated birth dates to test for breeding seasonality and calculated birthrates. Results Breeding was seasonal, and birthrates were low relative to other neotropical primates. We recorded unexpectedly high numbers of reproductively inactive females compared to other neotropical monkeys. Conclusions Reproductive inactivity could be due to delayed reproduction or long periods of lactation. Resource availability may also play a role. Slow reproduction and low birthrates in uakaris, relative other primates, could explain why uakaris have a patchy distribution and appear vulnerable to disturbance.